2009
DOI: 10.1016/j.ijrobp.2008.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Individual Positioning: A Comparative Study of Adjuvant Breast Radiotherapy in the Prone Versus Supine Position

Abstract: Conformal breast radiotherapy is feasible in the prone position. Its primary advantage is the substantially lower radiation dose to the ipsilateral lung. The higher dose inhomogeneity and increased rate of Grade 1-2 skin toxicity, however, may be of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 28 publications
(53 reference statements)
8
74
3
1
Order By: Relevance
“…This is the first study to analyse target and OAR dose compliance differences due to imaging modality (CT vs MRI) for target volume determination, in both supine and prone positions, although several groups have examined differences in supine and prone positioning for WB radiotherapy (Table 6) [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first study to analyse target and OAR dose compliance differences due to imaging modality (CT vs MRI) for target volume determination, in both supine and prone positions, although several groups have examined differences in supine and prone positioning for WB radiotherapy (Table 6) [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors report that prone positioning is better at heart dose and/or volume sparing than supine [15-17, 20, 23]. Some have reported no significant difference in heart dose between prone and supine positions [19,22]. One group identified a significant benefit of prone positioning on heart doses for women where the WB_CTV exceeded 1000 cm 3 for WB radiotherapy [18].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…However, limitations of the study included potential overestimation of set-up errors through use of a patient contour-based match sensitive to soft-tissue distortions, recruitment of 15 patients over a 13-month period, and use of two treatment machines and multiple teams of therapists. More recently, set-up data has been published on 41 patients randomized to supine versus prone treatment (11). Each patient underwent a pre-RT CT-simulator plan-check, and EPI (3 times per week) on treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Prone set-up yields the same advantages of lateral decubitus RT with a simpler set-up and better accuracy. Moreover, several studies have investigated prone RT where dosimetric studies 22,28 showed increased homogeneity and reduced lung doses with prone positioning in comparison with supine positioning, whereas in a large single-centre study by Stegman et al, 29 that reviewed the data of 245 patients treated over a 12-year period, planning was with opposed coplanar beams and the median hot spot percentage was 106% (interquartile range 104-108%) in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%